2018
DOI: 10.1016/j.ejor.2018.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Switching from oil to gas production in a depleting field

Abstract: We derive an optimal decision rule with regards to making an irreversible switch from oil to gas production. The approach can be used by petroleum field operators to maximize the value creation from a petroleum field with diminishing oil production and remaining gas reserves. Assuming that both the oil and gas prices follow a geometric Brownian motion we derive an analytical solution for the exercise threshold. We also propose an explicit solution for the option value that is new to the literature. Numerical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…We set the production cost of EVs c to 85000, and due to the maturity of traditional FV production technology, we assume that the production cost of FVs c0 is 50,000. Following Comincioli et al (2021), we take into account that r=0.03, and consistent with Støre et al (2018), we set α1,0.1emα2,0.1emσ1, and σ2 to 0.004, 0.005, 0.338, and 0.267, respectively. For the parameters of the dual credit policy, according to the statistics of MIIT (2022), we consider that the credit value obtained for each new energy vehicle is 3, and the average negative fuel consumption credit δ is 2.…”
Section: Numerical Simulationmentioning
confidence: 97%
See 2 more Smart Citations
“…We set the production cost of EVs c to 85000, and due to the maturity of traditional FV production technology, we assume that the production cost of FVs c0 is 50,000. Following Comincioli et al (2021), we take into account that r=0.03, and consistent with Støre et al (2018), we set α1,0.1emα2,0.1emσ1, and σ2 to 0.004, 0.005, 0.338, and 0.267, respectively. For the parameters of the dual credit policy, according to the statistics of MIIT (2022), we consider that the credit value obtained for each new energy vehicle is 3, and the average negative fuel consumption credit δ is 2.…”
Section: Numerical Simulationmentioning
confidence: 97%
“…Based on the previous research and in conjunction with the theorem 1 ofStøre et al (2018), The option value in the postponed region can be derived by finding min be used to calculate the option value for a given FV demand and credit price (x 1 ,p v1 ) in the postponed region: (1) Substituting the provided (x 1 ,p v1 ) into Equation (26) and solving this equation with a numerical technique to determine the threshold p v1 * . (2) Determine A,β, and η using the solution for p v1 * in Equations (A2), (A4) and (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the approach presented in Støre et al (2018) to solve this system, we found the explicit solution for the boundary 3 : b…”
Section: The Quasi-analytical Approachmentioning
confidence: 99%
“…Adkins and Paxson (2016) consider the optimal investment policy for an energy facility with price and quantity uncertainty under different subsidy schemes. Støre et al (2018) determine the optimal timing to switch from oil to gas production in the tail production phase, with the price of oil and gas following (correlated) Geometric Brownian motions. Finally, we refer to Heydari et al (2012), who extend the quasi-analytical approach proposed in Adkins and Paxson (2011b) to a three-factor model, which is employed to value the choice between two emission reduction technologies, assuming that the value of each option depends on fuel, electricity and CO 2 prices, all following (correlated) Geometric Brownian motions.…”
Section: Introductionmentioning
confidence: 99%